Development of the composition and technology of suspension for oral administration based on a solid dispersion of albendazole - Yu. I. Tikhomirova; N. O. Karabintseva; V. I. Evseenko; E. S. Meteleva; A. V. Dushkin; M. V. Zelikman (Разработка и регистрация лекарственных средств, 2025)
Introduction. The use of the method of mechanochemical synthesis to obtain solid dispersions (SD) of albendazole (ALB) has allowed increasing its anthelmintic activity and bioavailability, as well as reducing its toxicity, and therefore the issue of developing the composition and technology of an affordable domestic drug based on SD of ALB in a rational dosage form (DF) is relevant.Aim. Development and pharmacotechnological study of suspension for oral administration based on TD ALB obtained by mechanochemical solid-phase synthesis.Materials and methods. The objects of the study were ALB substance (ALB), licorice dry extract (LE) and their SD obtained by mechanochemical solid-phase synthesis in a mass ratio of 1 : 5, 1 : 10 and 1 : 20, with a mechanical treatment duration of 2 hours, 8 hours and 16 hours. Substances approved for medical use are used as excipients. The study of the solubility of ALB from SD was evaluated by the content of ALB in an aqueous medium using high-performance liquid chromatography. The study of the properties of SD and the obtained DF was carried out in accordance with the requirements of the State Pharmacopoeia of the Russian Federation (SP RF) XV edition.Results and discussion. The technological properties of SD do not change significantly depending on the mass ratio of medicinal substance (MS) to the carrier and the time of their machining, as a result of which the determining factor in choosing the optimal SD for the development of a DF is the value of the solubility of ALB in water. The use of the wet granulation method and the addition of a filler, stabilizer and preservative to the SD make it possible to obtain powders for the preparation of a suspension with satisfactory technological characteristics.Conclusion. During the study, the technological characteristics of SD ALB with LE obtained by mechanochemical solid-phase synthesis were studied, and the optimal SD was determined from the point of view of the highest solubility of ALB in water. Excipients were selected, the composition of the suspension restored from SD ALB granules with optimal technological parameters was developed. Pharmacotechnological studies of suspensions based on SD ALB were conducted.